Viability of sclerotia of Sclerotinia sclerotiorum at different depths and durations in soil: VIABILITY OF SCLEROTIA OF SCLEROTINIA SCLEROTIORUM AT DIFFERENT DEPTHS AND DURATIONS - RAKESH; A S RATHI; HAWA SINGH (Journal of Oilseeds Research, 2015)
Sclerotia of Sclerotinia sclerotiorum (Lib.) de Bary obtained fromnatural infected stemofIndianmustard plants were wrapped in synthetic nets and buried at different depths and durations under screen house and field conditions at CCS Haryana Agricultural University, Hisar. Viability of sclerotia was tested and it declined gradually in screen house and sharply under natural field conditions with the increase in soil depth and duration of burial. A maximum of 91.3 per cent sclerotial germination was found, when sclerotia were placed at soil surface (0 cm) for three months under screen house conditions while 83.8 per cent at same depth and duration under field conditions. A minimum of 8.8 per cent sclerotia germinated when placed below 12.5 cmdepth for six months under screen house conditions, while none of the sclerotia germinated, when placed below 5 cm for six months under field conditions.